"Interfaz web al software de alineamiento múltiple de secuencias con metaheuristica multiobjetivo (M2ALIGN)" - Soria Brito, Jefferson Edilberto (2017)
The main objective of this research is provide the scientific community with a web interface for quick and easy use to the multi-objective optimizer software for the Multiple Sequence Alignment (M2Align) called W-M2Align. Among the main functionalities of this web platform are the following input parameters: Sequences File: Set of unaligned biological sequences in FASTA format. Number of Evaluations: The maximum number of algorithm evaluations. Population Size: Size of the population of the algorithm Email: To receive the link with the execution results (Multiple Sequence Alignments and an approximation of the Pareto Front). Pre-computed Alignments: MSA’s performed by others heuristic tools to generate the initial solutions of the algorithm. All calculations are performed by a dedicated web-server with more than 60 cores for computational processing and the users receive the results via URL or email. It allows to perform a monitoring of the processes through its states (Running, Finished or Error), as well as the possibility of downloading the files of the execution. W-M2Align is available at http://bioinformatic.uteq.edu.ec/m2align/. It is free and open to all users and there is no login requirement. Keywords: Web Interface, Multiple Sequence Alignment, MultiObjective Optimization